1972
DOI: 10.1111/j.1432-1033.1972.tb19711.x
|View full text |Cite
|
Sign up to set email alerts
|

Gene Linkage and Gene‐Enzyme Relations in the Fatty‐Acid‐Synthetase System of Saccharomyces cerevisiae

Abstract: I n Saccharomyces cerevisiae, the genetic linkage as well as the biochemical characteristics of nine different fatty-acid-synthetase complementation groups have been studied. By spore tetrad analysis, the alleles of these nine groups were established to be located on three genetpically unlinked DNA regions on the yeast genome. These regions consist of one separate gene and two clusters comprising two and three adjacent cistrons, respectively. In both clusters the alleles are closely linked within less than one… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
17
0

Year Published

1973
1973
2004
2004

Publication Types

Select...
5
2
1

Relationship

2
6

Authors

Journals

citations
Cited by 60 publications
(18 citation statements)
references
References 9 publications
1
17
0
Order By: Relevance
“…A new concept of the yeast fatty acid synthetase has emerged and is based on comprehensive genetic and biochemical analyses by Schweizer and his colleagues (Schweizer et al, 1973;Schweizer and Bolling, 1970;Kuhn et al, 1972;Knobling et al, 1975;Schweizer et al, 1971;Tauro et al, 1974;Schweizer et al, 1978). The evidence suggests that the yeast fatty acid synthetase is composed of two multifunctional proteins, designated a and S, with molecular weights of 185,000 and 180,000 daltons, respectively.…”
Section: Polmityl-transfermentioning
confidence: 99%
“…A new concept of the yeast fatty acid synthetase has emerged and is based on comprehensive genetic and biochemical analyses by Schweizer and his colleagues (Schweizer et al, 1973;Schweizer and Bolling, 1970;Kuhn et al, 1972;Knobling et al, 1975;Schweizer et al, 1971;Tauro et al, 1974;Schweizer et al, 1978). The evidence suggests that the yeast fatty acid synthetase is composed of two multifunctional proteins, designated a and S, with molecular weights of 185,000 and 180,000 daltons, respectively.…”
Section: Polmityl-transfermentioning
confidence: 99%
“…Determining the molar amounts of substrate bound per mole of enzyme, Even though the individual ␣␤ monomer of yeast FAS is possibly capable of palmitic acid synthesis, cooperation between both identical and nonidentical subunits within the ␣ 6 ␤ 6 oligomer has in fact been demonstrated. Genetic complementation studies with yeast mutants which were specifically defective in one of the various FAS domains revealed that overall FAS activity was always restored, both in vitro and in vivo, whenever two mutations which affected two different catalytic activities were combined (74,140,178). For complementation, it was irrelevant whether the affected domains were located on the same or on two different subunits (140,178).…”
Section: Negative Cooperativitymentioning
confidence: 99%
“…The results hereby obtained suggested that especially the mutants of the fas-complementation groups 111, IV, I X and VII contained little or no radioactively labeled fatty acid synthetase. Among them, only the mutants of the nonpleiotropic complementation group VII produce a fatty acid synthetase like crossreacting material, whereas from mutants of the pleiotropic complementation groups 111, IV and I X in general no fatty acid synthetase complex can be isolated [13]. To confirm these preliminary results, in this study all 19 mutants available of fas-complementation group VII were grown in a [l4C]pantothenate-Iabeled medium and, subsequently, the radioactivity associated with their completely purified fatty acid synthetases was determined.…”
Section: Incorporation Of [14c]pantothenic Acid Into the Fattyacid-symentioning
confidence: 99%
“…Thus, fatty acid synthetase is not adsorbed to the gel and can be precipitated from the supernatant by ammonium sulfate. After two subsequent sedimentations in a Spinco L50 preparative ultracentrifuge as described earlier [13], the enzyme was finally purified by a sucrose density gradient ( 10-25°/,) centrifugation for 15 h at 100000 x g. After the run, the tubes were punctured a t the bottom and 25-drop fractions were collected and examined for their absorbance a t 280 nm. Radioactivity was determined by mixing 0.5 ml of each fraction with 18 ml of a scintillator solution containing, per liter dioxane, 100 g naphthalene, I0 g PPO and 0.25 g POPOP.…”
Section: Enzyme Purification and Assaysmentioning
confidence: 99%
See 1 more Smart Citation